Economic Liberalization and Its Impacts on the Manufacturing Industry in Sri Lanka - Amirthalingam, Kopalapillai (My University, 2008)
The economic performance of post independent Sri Lanka has improved only after the introduction of liberalization policies in 1977. Though many factors contributed for the sluggish performance of the economy during 1948-1977, the delay of industrialization is identified as contributing prime factor to the slow performance of the economy. However, after the liberalization, manufacturing sector started to play an important role in the economy in production, export earnings and employment in which agricultural sector held its domination since independence. Nonetheless, after three decades, the economy still overwhelmingly depends on garments and textiles industry for the production, export earnings and employment. Though the destructive civil war which started shortly after the introduction of liberalization policies has had harmful impact on the overall performance of the economy, Sri Lankan export-led industrialization has yielded relatively better outcome. If the country takes further measures to move gradually towards the production of hard manufacturing goods (such as electronic goods) the outcome of the export-led industrialization would be superior in the future.